2007
DOI: 10.1097/hjh.0b013e328048d004
|View full text |Cite
|
Sign up to set email alerts
|

The sympathetic nervous system and the metabolic syndrome

Abstract: Studies performed in the past two decades have unequivocally shown that several of the components of the metabolic syndrome are associated with indirect and direct markers of adrenergic overdrive. This is the case for hypertension and obesity, in which resting tachycardia, elevated plasma norepinephrine values, increased sympathetic nerve traffic, as well as augmented levels of total and regional norepinephrine spillover have been reported. This is also the case for insulin resistance, i.e. a metabolic conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
245
0
18

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 348 publications
(273 citation statements)
references
References 134 publications
10
245
0
18
Order By: Relevance
“…Furthermore, several studies identified in obese subjects an increase in plasma catecholamine levels (35,37), cardiovascular autonomic abnormalities, and activation in renin-angiotensin system (18). Moreover, the sympathetic nervous system seems to play a primary role in metabolic and cardiovascular alterations present in metabolic syndrome (18,23,29).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies identified in obese subjects an increase in plasma catecholamine levels (35,37), cardiovascular autonomic abnormalities, and activation in renin-angiotensin system (18). Moreover, the sympathetic nervous system seems to play a primary role in metabolic and cardiovascular alterations present in metabolic syndrome (18,23,29).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Many mechanisms also influence the positive correlation between MetS and IOP, but the direct mechanism for this is currently unknown. Sympathetic hyperactivation, 39 and aquaporins that are known to be related with insulin resistance 40 are considered as potential pathophysiological mechanisms of the relationship between MetS and IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Modest restriction of salt intake, low intake of saturated fats and cholesterol with increased consumption of fruits, vegetables and whole grains is recommended. 79,80 Moderate physical activity should accompany every dietary program. 81 Supplementary behavioral therapy including self-monitoring, psychological support and stress management could also be helpful.…”
Section: Endothelial Dysfunction and Changes In Vascular Structurementioning
confidence: 99%